Activation of «COVID» Words in the Kazakh Language: Statistical Analysis - Zhazira Agabekova; Aigul Amirbekova; Kalamkas Kalybekova; Dana Ospanova; Bayan Abylayeva; Bolat Khassenov (Bilingual Publishing Group, 2024)
Some words in the Kazakh language became more active during the pandemic. This article describes which words were most often used in the Kazakh language during the COVID-19 pandemic. The research materials were taken from Google Trends and the National Corpus of the Kazakh language. The analysis showed that in the Kazakh language words like koronavırýs-coronavirus (noun); covid (noun); COVID-19 (noun); pandemıa-pandemic (noun); koronavırýstyq ınfeksıa-coronavirus infection (adjective+ noun); karantın-quarantine (noun); ózin-ózi oqshaýlaý-self-isolation (pronoun+gesture name); lokdaýn-lokdaun (noun); áleýmettik qashyqtyq-social distance (adjective+noun); qashyqtyqtan oqytý-distance learning (noun+gesture name) were frequently used. The article has developed a visualization of the frequency of use of words with statistical diagrams.
Keywords: Kazakh; Coronavirus disease 2019 (COVID-19); 2019-20 coronavirus outbreak; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); Linguistics; Natural language processing; Computer science; Virology; Biology; Medicine; Outbreak; Philosophy; Disease; Pathology; Infectious disease (medical specialty); type of access: open access